Prevalence and Factors Associated with Burnout among Libyan Radiologists: A Cross Sectional Study - Enas Alhaen; Ibrahim, Olla; Ahmed Elhain (AlQalam Journal of Medical and Applied Sciences, 2025)
Burn-out syndrome is defined by world health organization as a syndrome resulted from chronic unmanaged work-place stress. It is considered as a raising psychological concern among health-related communities due to its series impacts on quality of health services and worker performance as well as mental health of health workers. Work related burnout happens usually amongst doctors than among those work in other jobs. Globally, researches showed escalating prevalence of burn out among radiologists. There is a lack of research regarding this topic in Libya. Therefore, the aim of this paper is to analyses the prevalence of burn out and possible associated factors among radiologists in Al-Baida Medical Centre (AMC). A cross sectional observational study carried out by using a structured survey including 3 main sections; demographic, possible associated factors and Maslach Burnout Inventory Human Services Survey (MBI-HSS). A data from 25 radiologists collected and analyzed with correlation via cross tables (Pearson- Chi-square). The result revealed about 80% of surveyed radiologists experiencing moderate to high level of burn-out syndrome. Correlation was significant between Burnout Emotional exhaustion and administrative task and being a member of teaching staff (r= 6.92, p< .05) and (r=5.8, p <0.05). Interestingly 96% stated stress during work is considerably reduced if a second opinion offered by expert colleagues. 76% of surveyed radiologists admitted extended their working hours and 44% of them doing that frequently. Spuriously, almost half of radiologists consider give-up and changing their career. While nearly 70% stated that their work affecting their family life. The result of this paper is consistent with other western countries. However, a further detailed national study is required to further investigate this health-related paradigm and necessitate the action to mitigate the negative impact of this syndrome. تعرف متلازمة الإحتراق من قبل منظمة الصحة العالمية بأنها متلازمة ناتجة عن ضغوط العمل المزمنة الغير معالجة ويعتبر هذا الأمر مصدر قلق متزايد بين المجتمعات المرتبطة بالصحة بسبب تأثيراته على جودة الخدمات الصحية وأداء العاملين وكذلك الصحة العقلية للعاملين في مجال الصحة. يحدث الإحتراق المرتبط بالعمل بين الأطباء أكثر من أولئك الذين يعملون في وظائف أخرى. وعلى مستوى العالم أظهرت الأبحاث انتشارا متزايدا للإحتراق بين أخصائيي الأشعة. هناك نقص في الأبحاث المتعلقة بهذا الموضوع في ليبيا لذلك فان الهدف من هذه الورقة هو تحليل انتشار الإحتراق الوظيفي والعوامل المرتبطة المحتملة بين أخصائيي الأشعة في مركز البيضاء الطبي ليبيا . دراسة مقطعية رصدية أجريت باستخدام مسح منظم يتضمن 3 أجزاء رئيسية:المعلومات الديموغرافية والعوامل المرتبطة المحتملة ومسح الخدمات البشرية لمخزون الإحتراق ماسلاك. تم جمع البيانات من 25 أخصائي أشعة و تحليلها باستخدام الارتباط عبر الجداول المتقاطعة. كشفت النتيجة أن حوالي 80% من أخصائيي الأشعة الذين شملهم الاستطلاع يعانون من مستوى متوسط إلى مرتفع من متلازمة الإحتراق. كان الارتباط مهما بين الإحتراق العاطفي والمهمه الإدارية وكونه عضوا في هيئة التدريس(r=6.92, p˂0.05) و( (r=5.8, p˂0.05ومن المثير للاهتمام إن 96% ذكروا إن الإجهاد أثناء العمل ينخفض بشكل كبير إذا قدم زملاء خبراء رأيا ثانيا. واقر 76% من أطباء الأشعة الذين شملهم الاستطلاع بتمديد ساعات عملهم و 44% منهم يفعلون ذلك بشكل متكرر. فكر تقريبا نصف أطباء الأشعة المشاركين في الاستطلاع في التوقف وتغيير حياتهم المهنية بينما ذكر ما يقرب من 70% إن عملهم يؤثر على حياتهم الأسرية، وتتفق نتيجة هذه الورقة مع الدول الغربية الأخرى. مع ذلك هناك حاجة إلى دراسة محلية مفصلة أخرى لمزيد من التحقيق في هذا النموذج المتعلق بالصحة وضرورة اتخاذ إجراءات للتخفيف من التأثير السلبي لهذه المتلازمة